2018
DOI: 10.3892/mmr.2018.9758
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative drugs for gastric adenocarcinoma utilizing differentially expressed genes and connectivity map

Abstract: Gastric adenocarcinoma (GAC) is a challenging disease with dim prognosis even after surgery; hence, novel treatments for GAC are in urgent need. The aim of the present study was to explore new potential compounds interfering with the key pathways related to GAC progression. The differentially expressed genes (DEGs) between GAC and adjacent tissues were identified from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) database. Connectivity Map (CMap) was performed to screen candidate compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Owing to the high incidence and mortality of GC, it is urgent to understand its underlying molecular mechanism to discover new biomarkers [ 17 ]. DEGs between GC and adjacent tissues are identified from TCGA and GTEx databases [ 18 ]. This study aimed to explore and verify the possible key factors in the p53 signaling pathway that participated in the initiation and progression of GC using GTEx and TCGA databases.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the high incidence and mortality of GC, it is urgent to understand its underlying molecular mechanism to discover new biomarkers [ 17 ]. DEGs between GC and adjacent tissues are identified from TCGA and GTEx databases [ 18 ]. This study aimed to explore and verify the possible key factors in the p53 signaling pathway that participated in the initiation and progression of GC using GTEx and TCGA databases.…”
Section: Discussionmentioning
confidence: 99%
“…The latest statistics from the American Cancer Society showed that approximately 26,380 new cases of GC are projected to occur in 2022, of which 11,090 cases are likely to result in death 4 . In terms of treatment technology, although neoadjuvant chemoradiotherapy and targeting therapy are believed to be effective, surgery has proven to be the sole radical treatment 5–8 . Contemporarily, the survival rate of patients with early GC was more than 95% owing to surgical improvements, the development of chemotherapy and radiotherapy, and the practice of neoadjuvant treatments.…”
Section: Introductionmentioning
confidence: 99%
“… 4 In terms of treatment technology, although neoadjuvant chemoradiotherapy and targeting therapy are believed to be effective, surgery has proven to be the sole radical treatment. 5 , 6 , 7 , 8 Contemporarily, the survival rate of patients with early GC was more than 95% owing to surgical improvements, the development of chemotherapy and radiotherapy, and the practice of neoadjuvant treatments. Nevertheless, the difficulty with early detection has led to the fact that the majority of patients have been diagnosed at late stages and have thus failed to undergo optimal surgical treatment.…”
Section: Introductionmentioning
confidence: 99%